2020
DOI: 10.1111/epi.16663
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant vigabatrin toxicity during combination therapy with adrenocorticotropic hormone for infantile spasms: Three cases and review of the literature

Abstract: Adrenocorticotropic hormone (ACTH), prednisone, and vigabatrin (VGB) are first-line treatments for infantile spasms (IS). 1 The antiseizure properties of VGB, an irreversible inhibitor of γ-aminobutyric acid (GABA) transaminase, are thought to emerge from increased levels of GABA. VGB can produce significant adverse effects, including irreversible visual field defects, movement disorders, and vigabatrin-associated brain abnormalities on magnetic resonance imaging (VABAM). 2,3 VABAM, characterized by diffusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…17 Pearl et al 18 reported a case of sudden epileptic death in a child with a 13-month history of VGB exposure, and the autopsy report indicated that spongy white matter was vacuolated, including medullary reticulum. In the study of Bhalla et al, 8 a child with epilepsy taking VGB developed fulminant VGB toxicity, and autopsy results suggested spongiform vacuolar edema throughout the white matter tract and typical VABAM area, which was associated with fatal encephalopathy. The vacuolar edema in the above study cases and animal models may explain the abnormally high signal on DWI in the VABAM group.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…17 Pearl et al 18 reported a case of sudden epileptic death in a child with a 13-month history of VGB exposure, and the autopsy report indicated that spongy white matter was vacuolated, including medullary reticulum. In the study of Bhalla et al, 8 a child with epilepsy taking VGB developed fulminant VGB toxicity, and autopsy results suggested spongiform vacuolar edema throughout the white matter tract and typical VABAM area, which was associated with fatal encephalopathy. The vacuolar edema in the above study cases and animal models may explain the abnormally high signal on DWI in the VABAM group.…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies have shown that VGB exposure may cause vigabatrin‐associated brain abnormalities on magnetic resonance imaging (MRI) (VABAM), that is, the reversible high T2‐weighted imaging (T2WI) signal and diffusion restriction of the thalamus, basal ganglia, brainstem, and cerebellar dentate nucleus. This phenomenon has not been reported in older children and adults, but the incidence of VABAM in infants could be as high as 21%–32% 8–11 . Although many studies have shown that this abnormality is usually reversible and is not accompanied by clinical symptoms, there are still some cases with movement disorders, encephalopathy, dysautonomia, or even death after the occurrence of VABAM 8 …”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…The presurgical assessment should be performed at an epilepsy center with pediatric expertise. If drug resistance is proven, the timing for the operation should be chosen as early as possible (►Table 14).…”
Section: Comment On Recommendation 10mentioning
confidence: 99%